I Feel I Need to Think about It: A Defence of Affective Moral Enhancement - Huang, Pei-hua (Bioethics, 2026)
Critics of affective moral enhancement generally contend that moral improvement can only be properly achieved through interventions that engage a person's rational faculties. Therefore, they view attempts to achieve moral improvement by targeting emotions as futile at best and detrimental to moral agency at worst. In this paper, I argue that even if we accept the view that genuine moral improvement requires the engagement of rational faculties, we need not reject all forms of affective moral enhancement. My argument premises on the view that certain types of affect are highly informative. Affective moral enhancement that aims to elicit these affective states grants enhancement recipients access to vital moral knowledge they may not be able to attain otherwise. I then introduce the distinction between two types of affect—emotions and moods—and argue that the concerns regarding affective moral enhancement only apply to interventions that aim to achieve moral improvement via direct mood modulation.